Significant discrepancies exist between clinician assessment and patient self-assessment of functional capacity by validated scoring tools during preoperative evaluation. Issue 1 (December 2016) - Stokes, John; Wanderer, Jonathan; McEvoy, Matthew
Abstract Background Preoperative assessment of functional capacity is necessary to direct decisions regarding cardiac evaluation and may help identify patients at high risk for perioperative complications. Patient self-triage regarding functional capacity could be useful for discerning which patients benefit from a clinician evaluation at a Preoperative Evaluation Center prior to the day of surgery. We evaluated the feasibility of preoperative, patient self-triage regarding functional capacity. Methods Patients were recruited immediately prior to their preoperative evaluation. Study participants completed electronic versions of the Duke Activity Status Index (DASI) and the Patient-Reported Outcomes Measurement System (PROMIS)–Short Form 12a–Physical Function. DASI and PROMIS questionnaire responses were scored and evaluated for correlation with clinician assessments of functional capacity. Correlation was analyzed around the dichotomous outcome of <4 metabolic equivalents of task (METs) or ≥4 METs. Patients also evaluated the usability of the questionnaires. Results After IRB approval, 204 patients were enrolled and completed both DASI and PROMIS questionnaires. Clinicians assessed functional capacity at <4 METs for 109 patients (53.4 %) compared to 18 (8.8 %) patient self-assessments <4 METs as estimated by DASI. These results represent a significant discrepancy between assessments (Fisher's exact, two-tailedP value <0.0001). The standard T-score of PROMIS estimates of functional capacity correlated with DASI estimates (R 2 0.76). The mean and standard deviation for PROMIS T-scores were 43.3 and 9.86, respectively (mean 50.0; SD 10.0 for the general population). Of the 203 patients who completed the entire study survey, 192 (94.6 %) stated that they did not require assistance from another person, and 187 (94 %) responded either "agree" or "strongly agree" to the DASI questionnaire being "easy to understand" and "easy to complete;" 186 (93 %) and 188 (94 %), respectively, responded similarly to the PROMIS questionnaire. Conclusions While both electronic questionnaires were easy to understand and complete for most study participants, there was a significant discrepancy between clinician assessments and patient self-assessments of functional capacity. Further study is needed to determine if either patient self-triage by means of activity questionnaires or clinician evaluation is valid and reliable in the preoperative setting.